Incomplete Shone’s complex with cor triatriatum sinister and interrupted aortic arch: Prenatal diagnosis of a rare association - Shaimaa Rakha (Annals of Pediatric Cardiology)
Shone’s complex is a rare constellation of multilevel left cardiac obstructive lesions involving both the inflow and outflow. Four primary lesions were included in the initial lesion description. However, other obstruction-causing structural lesions could be infrequently associated. The current report describes a fetal diagnosis of an unusual association of incomplete Shone’s complex with cor triatriatum sinister and interrupted aortic arch.